The Influence of Inflation and Interest Rates on MSME Turnover in Makassar City - Moh. Fajrin Ahmad (ProBisnis : Jurnal Manajemen, 2021)
This study aims to determine the effect of inflation and interest rates on MSME turnover in Makassar City. The type of data used is secondary data from library research, both quantitative and qualitative. The population in this study is all reports on inflation and interest rates as well as reports on the turnover of the Makassar City MSME Service. The sample is data from the last eleven years (2002 -2012) using data collection techniques, namely documentation. The technique of data analysis used is multiple linear regression analysis, f-test, and t-test. Simultaneously the comparison between F-count and F-table which shows that F-count > F-table, indicating that the independent variables together have a significant effect on the dependent variable, so that the variables of Inflation Rate (x1) and Interest Rates (x2) together have a significant effect on MSME Turnover in Makassar City at a significant level of 5%. Partially based on the results of the t-test analysis that has been carried out, it can be seen that: For the X1 variable (Inflation Rate) t-count < t-table so that the hypothesis is rejected where the inflation rate has no significant effect but has a positive effect on MSME turnover, while for the X2 variable ( Interest Rate) t-count > t-table so that the hypothesis is accepted where interest rates have a significant but negative effect on MSME turnover. The magnitude of the correlation between inflation rates and interest rates on MSME turnover is 0.655 where the relationship is classified as very strong or 65.